Entrepreneurial intensity: the influence of antecedents to corporate entrepreneurship in firms operating in South Africa - Scheepers, Margarietha Johanna (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Business Management))--University of Stellenbosch, 2007.